Establishment of a Legal Aid Post to Increase Legal Awareness of the Candijati Village Community Towards a Legally Aware Village - Nanda Bagus Putra; Annisa Aulia; Andriani (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
This Community Service Program was carried out in Candijati Village, Arjasa District, Jember Regency. There are several main problems in Candijati Village, namely, the lack of knowledge about the law makes the community prone to committing crimes, and the level of violence against children and women is quite high and in the context of optimizing the Candijati Village Community towards a law-aware village based on the concept contained in the Head of BPHN Regulation Number: PHN.HN.03.05-73 of 2008 concerning the Formation and Fostering of Law-Aware Families and Villages/Kelurahan Aware of Laws and Regulations of the Minister of Law and Human Rights of the Republic of Indonesia Number: M.01-PR.08.10 of 2007 concerning Amendments to Ministerial Regulations Law and Human Rights Number: M.01-PR.08.10 of 2006 concerning Patterns of Legal Counseling. This study describes comprehensively the implementation of the program for establishing legal aid posts in increasing community legal awareness towards a law-aware village which was carried out in Candijati village by the ORMAWA Asean Law Student Association Local Chapter University of Jember 2023 implementation team. The process of increasing public knowledge in the field of law This is carried out through three approaches, namely socialization, counseling, and the establishment of legal aid posts.